A multi-step analysis and co-produced principles to support equitable partnership with Liverpool School of Tropical Medicine, 125 years on. - Robinson Karuga; Rosie Steege; Shahreen Chowdhury; Bertie Squire; Sally Theobald; Lilian Otiso (PLOS Global Public Health, 2024)
Transboundary health partnerships are shaped by global inequities. Perspectives from the "global South" are critical to understand and redress power asymmetries in research partnerships yet are not often included in current guidelines. We undertook research with partners working with the Liverpool School of Tropical Medicine (LSTM) to inform LSTM's equitable partnership strategy and co-develop principles for equitable partnerships as an entry point towards broader transformative action on research partnerships. We applied mixed-methods and participatory approaches. An online survey (n = 21) was conducted with LSTM's transboundary partners on fairness of opportunity, fair process, and fair sharing of benefits, triangulated with key informant interviews (n = 12). Qualitative narratives were analysed using the thematic framework approach. Findings were presented in a participatory workshop (n = 11) with partners to co-develop principles, which were refined and checked with stakeholders. Early inclusion emerged as fundamental to equitable partnerships, reflected in principle one: all partners to input into research design, agenda-setting and outputs to reflect priorities. Transparency is highlighted in principle two to guide all stages including agenda-setting, budgeting, data ownership and authorship. Principle three underscores the importance of contextually embedded knowledge for relevant and impactful research. Multi-directional capacity strengthening across all cadres is highlighted in principle four. Principle five includes LSTM leveraging their position for strategic and deliberate promotion of transboundary partners in international forums. A multi-centric model of partnership with no centralised power is promoted in principle six. Finally, principle seven emphasises commitment to the principles and Global Code of Conduct values: Fairness, Respect, Care, Honesty. The co-developed principles are part of ongoing reflections and dialogue to improve and undo harmful power structures that perpetuate coloniality within global health. While this process was conducted with LSTM-Liverpool's existing partners, the principles to strengthen equity are applicable to other institutions engaged in transboundary research partnerships and relevant for funders.